The Effects Of Employee Motivation And Employee Satisfaction On E-Leadership In Business Service Industry - Nur Balqis, Norizal (2024)
In response to the rapid digitization and the global COVID-19 pandemic, numerous businesses have transitioned to remote work arrangements. As a result, this research aims to explore the interplay between employee motivation, satisfaction, and eleadership within the context of remote work environments, with a specific focus on employees in the business services industry. Statistical analysis techniques, including SPSS version 29, were employed to analyse the acquired data. Data was collected via structured online questionnaires distributed to employees. The research revealed a significant relationship between employee motivation, satisfaction, and eleadership. The results also revealed that effective e-leadership practices play a crucial role in influencing employee well-being and productivity. Finally, these results offer theoretical, and practical implications and will help academics and practitioners in human resource management field. Recommendations for further research in this area were developed based on the analysis and discussion.